Pentagon Fraud Analysis in Detecting Fraudulent Financial Reporting - Eny Kusumawati; Ika Putri Yuliantoro; Eskasari Putri (Universitas Muhammadiyah Surakarta, 2021)
The purpose of this study was to analyze the influence of fraud pentagon theory in detecting the fraudulent financial reporting. Fraud pentagon theory is the development of the previous fraud theory of fraud triangle and fraud diamond. This research uses eight variables that are hypothesized to affect fraudulent fianncial reporting. The population in this study are manufacturing companies basic industrial and chemical sector listedon the Indonesia Stock Exchange (IDX) during the 2017-2019. The sample was determined by purposive sampling technique and obtained a sample of 105 companies. This research uses statistical analysis by regression analysis. The results in this study are financial target, external pressure, institusional ownership, and capability had effect in detecting fraudulent financial reporting. Financial stability, opportunity, rationalization, and arrogance had no effect in detecting fraudulent financial reporting